MODIFICATIONS OF VOWELS IN THE CONNECTED SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the various modifications of vowels that occur in connected speech, highlighting how vowels in natural conversation often deviate from their isolated or dictionary pronunciations. The main types of vowel modifications discussed include reduction, elision, assimilation, diphthongization, and linking. Each modification serves to streamline speech, making communication more efficient and fluid by adjusting vowel sounds in unstressed syllables, blending adjacent sounds, or introducing transitional glides. The article emphasizes the importance of these modifications for language learners aiming for fluency, as well as for linguists studying phonetic patterns and dialectal variations. By understanding these adjustments, readers gain insight into the dynamic nature of spoken language and the role that vowel modifications play in enhancing the flow and comprehension of everyday speech.